Analisis Pengeluaran Pemerintah Dan Likuiditas Perekonomian Terhadap Pertumbuhan Ekonomi Di Indonesia - Mawaddah Dwi Putri; Aimon, Hasdi (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This study aims to analyze the impact of government spending and economic liquidity (M2) on economic growth in Indonesia. This study uses secondary data obtained from the publications of Bank Indonesia, the Central Bureau of Statistics, and the World Bank from 1991 to 2023. The dependent variable in this study is economic growth as measured by Gross Domestic Product (GDP), while the independent variables used are government spending and economic liquidity (M2). this study uses control variables, namely investment and trade. This study uses multiple linear regression with time series data. The results showed that government spending and economic liquidity (M2) significantly and positively affect economic growth in Indonesia. In addition, control factors such as investment show a positive impact, while trade shows a negative influence on economic growth. All the variables studied together have a considerable influence on economic growth in Indonesia